Effect of Floating Plants on Constructed Wetland Microbial Fuel Cell Treating Domestic Wastewater - Wahyuni, Afrinda Dwi; Yuniarto, Adhi; Arliyani, Isni; Min, Booki (Universitas Diponegoro, 2025)
Sustainable domestic wastewater treatment is urgently needed amid water scarcity and rising energy demands. The Constructed Wetland–Microbial Fuel Cell (CW-MFC) system integrates phytoremediation and bioelectricity production by electroactive microorganisms, yet previous studies rarely compared the synergistic effects of different plant species within this system, limiting its optimization. This study evaluated CW-MFC performance using three plant configurations (Pistia stratiotes, Eichhornia crassipes, and their combination) integrated with Lactobacillus plantarum at two concentrations (2×10⁸ CFU/mL and 5×10⁸ CFU/mL). The reactors were operated for 18 days under identical hydraulic conditions to assess BOD, COD, ammonia, and TSS removal efficiencies and power density generation. Results showed that Eichhornia crassipes achieved the highest pollutant removal efficiencies with COD reduction up to 82%, while the system with 2×10⁸ CFU/mL bacterial concentration produced the highest power density of approximately 1032 mW/m². Interestingly, lower bacterial concentrations yielded higher power outputs, possibly due to reduced microbial competition for electron transfer sites, enhancing electroactive bacteria performance. In conclusion, integrating Eichhornia crassipes with L. plantarum at 2×10⁸ CFU/mL optimizes both pollutant removal and bioelectricity production, confirming CW-MFC as an environmentally friendly technology with potential for sustainable wastewater treatment and renewable energy generation.